2021
DOI: 10.3390/healthcare9050516
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring in the Covid-19 Era: The Tuscany Region Experience

Abstract: Covid-19 has brought many difficulties in the management of infected and high-risk patients. Telemedicine platforms can really help in this situation, since they allow remotely monitoring Covid-19 patients, reducing the risk for the doctors, without decreasing the efficiency of the therapies and while alleviating patients’ mental issues. In this paper, we present the entire architecture and the experience of using the Tel.Te.Covid19 telemedicine platform. Projected for the treatment of chronic diseases, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Approximately 95% of health centers reported that such visits were conducted during the pandemic [8]. A recent study conducted by Panicacci et al (2021) presented a case of existing telemedicine system that was updated with new features to monitor and provide care to high risk COVID patients in their homes. This approach was extremely successful and led to a reduction in (or no) hospitalization, deaths, and positive feedback from patients and practitioners [9].…”
Section: Background and Rationalementioning
confidence: 99%
“…Approximately 95% of health centers reported that such visits were conducted during the pandemic [8]. A recent study conducted by Panicacci et al (2021) presented a case of existing telemedicine system that was updated with new features to monitor and provide care to high risk COVID patients in their homes. This approach was extremely successful and led to a reduction in (or no) hospitalization, deaths, and positive feedback from patients and practitioners [9].…”
Section: Background and Rationalementioning
confidence: 99%
“…In Italy, in the course of the first wave of the COVID-19 pandemic, available telehealth solutions have been used to track and promptly detect potentially infected individuals [ 14 , 15 ] and monitor patients with any critical chronic condition (including heart failure, diabetes, oncological disease, skin disease, neurological or psychiatric disease, immunological disease) restrained at home [ 16 22 ]. However, preliminary reports suggest that the Country was mostly unprepared to implement existing telehealth solutions for this purpose [ 11 , 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the state of telemedicine before the outbreak of COVID-19 needs mention. Until then, telehealth initiatives were organized locally within a disease-specific program ( 35 , 36 ) due to several issues, such as the lack of homogenous infrastructures and application standards or inadequate reimbursement for telemedicine services ( 35 , 37 ). So, without a nationwide telehealth system, the pre-existing limited telemedicine infrastructure was deployed during the first wave of the pandemic ( 36 ), in addition to the conventional phone calls or emails to the patients.…”
Section: Discussionmentioning
confidence: 99%